Dynamic bearing capacity of point fixed corrugated metal profile sheets subjected to blast loading. Issue 3 (September 2022) - Fischer, Kai; van der Woerd, Jan Dirk; Harwick, Wilfried; Stolz, Alexander
Blast loading scenarios and the corresponding hazards have to be evaluated for infrastructure elements and buildings especially at industrial sites for safety and security issues. Point fixed corrugated metal sheets are often applied as façade elements and can become a hazard for humans if they are pulled off. This paper investigates the dynamic bearing capacity of such structural members in terms of their general bending behavior in the middle of the span and pull-out behaviors at the fixing points. The elements are fixed at two sides and the load transfer is uniaxial. An experimental series with static and dynamic tests forms the basis to identify the predominant failure modes and to quantify the maximum stress values that can be absorbed until the investigated structural members fail. The experimental findings are applied to create and to optimize an engineering model for the fast and effective assessment of the structural response. The aim is the derivation of a validated model which is capable to predict the blast loading behavior of metal sheets including arbitrary dimensions, material properties, and screw connections. Results of this study can be integrated into a systematic risk and resilience management process to assess expected damage effects and the evaluation of robustness.